Ethnic boundaries and everyday understanding: the case of Malay and Chinese parental choice of National and National Type School in Peninsular Malaysia - Khauthar Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Since the pre-independence era, the Malaysian schooling system has remained ethnicized by two cultural boundaries: language and religion. To explain this situation, this article focuses on how these ethnic boundaries work within Malay and Chinese parents’ decisions for National and National Type of Schools, respectively. Thirty Malaysian Malays and 25 Chinese students born between the 1970s and the 1990s were interviewed in this research. The data showed that the majority of them had been enrolled in a primary and secondary school which could be associated with their ethnic identity. Analysis of the findings also suggested that despite the importance of future career planning, regionality and family socioeconomic background in the choice of schooling, it was the language and religious factors which had determined their parents’ final decision. It also suggested that a schooling pattern based on the factors of language and religion has been sustainably maintained for three decades. The parental decision was not a simple action as it is also related to the ‘everyday’ understanding of what kind of school is appropriate to a particular ethnic group. The results of this study offer a theoretical explanation of ethnicity in everyday life from the constructivist perspective. This study also highlights how ethnic boundaries are the end-product of a social process rather than a taken-for-granted, natural and primordial fact of life ascribed through birth.